Benefits and pitfalls of an EU emissions budget approach - Oliver Geden; Brigitte Knopf; Felix Schenuit (Stiftung Wissenschaft und Politik (SWP), 2023)
Following the conclusion of the 'Fit for 55' package, European Union (EU) climate policy will enter its next phase. One of the most important decisions will be how to set the economy-wide emissions reduction target for 2040, which will form the starting point for the next round of revisions of all EU climate policy legislation. The European Climate Law stipulates that the European Commission shall propose a 2040 target that is based, among other things, on a "projected indicative Union greenhouse gas budget for the 2030-2050 period", informed by a report of the newly established European Scientific Advisory Board on Climate Change. While cumulating emissions resulting from different future trajectories can help to assess ambition levels, strictly deriving a 'science-based' EU emissions budget from the global carbon budget has several pitfalls. The debate on the design of EU climate policy after 2030 should not put too much focus on the 'appropriate' target for 2040 but on how to further develop the governance architecture, strengthen policy instruments, and bolster public support.
Keywords: 320; EU emissions budget approach; EU climate policy; "Fit for 55" package; European Scientific Advisory Board on Climate Change; Paris Agreement; United Nations Framework Convention on Climate Change (UNFCCC)